A Review of Photogrammetry and Photorealistic 3D Models in Education From a Psychological Perspective - Nebel, Steve; Beege, Maik; Schneider, Sascha; Rey, Günter Daniel (Frontiers in Education, 2020)
Until sufficient practical experience and documented examples are available, emerging technological methods to create educational content typically require in-depth knowledge from different fields in order to apply them in the most beneficial way. The method of creating photorealistic 3D models (PR3DMs) of real-world objects with the methods of photogrammetry is an example of such emerging technologies. This paper discusses the fundamental concepts of photogrammetry to provide an overview of the necessary basic knowledge for educators and researchers interested in the presentation of realistic virtual materials. Additionally, a deeper introduction to basic psychological processes while learning with photorealistic materials is presented. This provides deeper insights into potentials and issues, as well as an overview of the most crucial research gaps in learning with PR3DMs. Finally, current and future applications, as well as the potential for learning topics apart from factual knowledge, such as emotional or behavioral outcomes, are discussed.